2011
DOI: 10.1007/s00213-011-2523-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial self-stimulation in FAST and SLOW mice: effects of alcohol and cocaine

Abstract: Rationale Sensitivity to the stimulant and rewarding effects of alcohol may be genetically-correlated traits that predispose individuals to developing an alcohol use disorder. Objective To examine the effects of alcohol and cocaine on intracranial self-stimulation (ICSS) in FAST and SLOW mice, which were selectively bred for extremes in alcohol stimulation. Methods Male FAST and SLOW mice were conditioned to respond for reinforcement by direct electrical stimulation of the medial forebrain bundle (i.e. bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 97 publications
(118 reference statements)
1
13
0
1
Order By: Relevance
“…The literature on brain reward function during ethanol intoxication is equivocal. While a number of studies, consistent with the present findings, report decreased (e.g., Schaefer & Michael, 1992) or unaltered brain reward function (e.g., Moolten & Kornetsky, 1990; Schaefer & Michael, 1987) by ethanol, other studies report ethanol-induced reward enhancement (e.g., Bain & Kornetsky, 1989; Bespalov et al, 1999; de Witte & Bada, 1983; Eiler et al, 2007; Fish et al, 2012; Lewis & June, 1990, 1994). Some of these discrepancies may be attributable to different experimental procedures.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The literature on brain reward function during ethanol intoxication is equivocal. While a number of studies, consistent with the present findings, report decreased (e.g., Schaefer & Michael, 1992) or unaltered brain reward function (e.g., Moolten & Kornetsky, 1990; Schaefer & Michael, 1987) by ethanol, other studies report ethanol-induced reward enhancement (e.g., Bain & Kornetsky, 1989; Bespalov et al, 1999; de Witte & Bada, 1983; Eiler et al, 2007; Fish et al, 2012; Lewis & June, 1990, 1994). Some of these discrepancies may be attributable to different experimental procedures.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, while the group mean data revealed no significant differences in the reward-enhancing effects of ethanol, exploratory analyses suggested that adolescent intermittent ethanol exposure may perhaps also increase sensitivity to the rewarding or appetitive effects of ethanol. Rodents selectively bred for high ethanol consumption show similar ethanol sensitivities (Chester et al, 2006; Eiler et al, 2007; Fish et al, 2012), suggesting that high sensitivity to ethanol reward and low sensitivity to ethanol withdrawal may predict heavy or problematic alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, Ewan and Martin used Fisher 344 rats, whereas this study used Sprague-Dawley rats. Strain differences can produce profound differences in drug effects in experimental assays including ICSS (Fish et al, 2012). Second, the previous study examined ICSS in the ventral tegmental area of the brain rather than the MFB.…”
Section: Discussionmentioning
confidence: 99%